Evaluation of Visitor Loyalty to Technology-Based Attractions for Sustainable Tourism at Taman Safari Indonesia after COVID-19 - Hasibuan, Ratna Sari; Soekmadi, Rinekso; Purnomo, Herry; Mulyono, Nur Budi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Taman Safari Indonesia (TSI) is an organization dedicated to ex-situ conservation. The pandemic caused a 53% decline in visitor visits to TSI in 2020 compared to 2019, creating an urgent need for funds to ensure the institution’s sustainability. In response, various technology-based visitor attractions have been developed, focusing on Augmented Reality (AR) applications to enhance both the quantity and quality of visitor experiences. This study examines how visitors’ experiences with technology-driven attractions influence their satisfaction and loyalty to TSI. The SEM-PSL method was used to analyze data using structural equation modeling. After using the AR features, they completed a questionnaire based on their impressions of AR-based visitors’ attractions. The results showed that the relationship between satisfaction and loyalty was significant, with a path coefficient of 3.760, greater than the t-table value of 1.96 at a 95% confidence level, indicating statistical significance. The findings suggest that higher satisfaction levels lead to greater visitor loyalty, with satisfied visitors more likely to return to TSI, especially with the enhanced AR experience. Visitors’ interactions with AR features improved their overall experience and strengthened their emotional connection to the TSI, suggesting the potential for sustained engagement. These results imply that integrating advanced technologies such as AR can play a key role in fostering visitor loyalty. Future tourism strategies should integrate immersive AR experiences with ecological education and conservation efforts to promote environmental sustainability.